The impact of physical activities on cognitive function among older adult populations: evidence from China - Xiao Chen; Xiao Chen; Qishun Yang; ZhiYun Liu (Frontiers in Public Health)
ObjectiveThis study investigates the impact of physical activity on cognitive function in Chinese middle-aged and older adult individuals, examining the relationship between different intensities of physical activity and cognitive function, as well as the effect of physical activity on various types of cognitive function.MethodA total of 27,529 samples were selected from the China Health and Retirement Longitudinal Study (CHARLS) data from 2011 to 2018 for regression analysis. Multidimensional fixed effects estimation was used to validate the impact of physical activity on cognitive function in middle-aged and older adults, analyzing differences in the intensity of physical activity and types of cognitive function. The empirical results were further tested using methods such as propensity score matching (PSM). Additionally, this paper conducted heterogeneity analyses by gender, place of residence, presence of children, and marital status.ResultsPhysical activity had a positive impact on cognitive function among middle-aged and older adults in China by improving their cardiovascular health, and this result held true regardless of gender, rural or urban residence, presence of children, or marital status. This conclusion was supported by both alternative explanatory variables and results from propensity score matching. Further research found that physical activity improves immediate memory and delayed recall among middle-aged and older adults. Moderate physical activity enhances the health of the older adult population, whereas excessive physical activity may impair cognitive function in middle-aged and older adults.ConclusionOur study found that PA can effectively promote the improvement of cognitive function in middle-aged and older adults, with this conclusion still holding true in older populations. Such physical activity should be moderate, because vigorous physical activity may impair cognitive function in middle-aged and older people. The study conclusions play a significant role in promoting physical activity, delaying cognitive decline, achieving active aging, and reducing the burden of informal caregiving.